Finance and protection of investments in developing countries - Detter Delupis, Ingrid (Epping : Gower Press, 1973)
The book attempted to establish the balance of interest between developing countries and foreign investors. It also examines the legal framework of foreign investment and rules concerning nationalization and expropriation of foreign-owned enterprises.
Includes index
Includes bibliographical references.
usc11/04/2018; 07/08/2018
Loans
Keywords: Investments, Foreign; Investments, Foreign--Law and legislation; Finance; Developing countries